PELAKSANAAN PEMBELAJARAN SENI MUSIK KELAS IV SD N PALEBON 01 KOTA SEMARANG TAHUN AJARAN 2023/2024 - Eri Widiana; Wawan Priyanto; Riris Setyo Sundari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The background that drives this research is that music learning in schools aims to help students develop creative attitudes and skills. So in the implementation of music learning at school, students have the right to gain musical experience. The focus of this research is on how the implementation of fourth grade music learning at SD N Palebon 01 in the 2023/2024 academic year. The purpose of this study is to analyze the implementation of fourth grade music learning at SD N Palebon 01 in the 2023/2024 school year from preparation, process, evaluation, to the components used in learning. This type of research is descriptive qualitative. Using interview, questionnaire and documentation methods. The subjects of this study were teachers and students of SD N Palebon 01 Semarang City. The results of this study are to find out that the fourth grade teacher of SD N Palebon 01 Semarang City in implementing Music Arts learning uses the Merdeka Curriculum in Phase B. There are several findings in the implementation of learning Music Arts at SD N Palebon 01 Semarang City, namely: 1) Preparation Stage; 2) Process Stage, including introduction, core and closing; 3) Evaluation Stage, including process evaluation and summative evaluation.